PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI KELAS X SMK NEGERI 1 SIBUHUAN - Melida Warni Nasution; Yuni Rhamayanti; Nova Christina Dewi (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2022)
This study uses problem solving methods in the experimental class A and the cooperative method with the type of Guided Inquiry in the experimental class B. In research that uses problem solving learning, students' mathematical problem solving abilities in experimental class A will be seen. Data on students' mathematical problem solving abilities are obtained by providing description test as many as 5 questions on the pretest and posttest. From previous research data, the researcher obtained tcount = 1.950 and ttable = 1.670. This indicates that the learning outcomes taught using problem solving methods are different from problem solving abilities using the cooperative method of Guided Inquiry. Meanwhile, in the cooperative model of the type of Guided Inquiry, the class became a little noisier and slower because of the change in groups from the initial group to the expert group and from the expert group back to the initial group again. The results of these calculations indicate that the problem solving method and the cooperative method of the type of Guided Inquiry have differences in students' mathematical problem solving abilities. The test results on the problem-solving method and the cooperative method of the Guided Inquiry type showed that students had the ability to state what was contained in the problem into a mathematical model and students could express the correct reasons for the questions given.